Principles and assumptions of psychometric measurement - Gavin T. L. Brown (Universidad Peruana de Ciencias Aplicadas, 2023)
Introduction: the validity of claims about learner self-reports depends on the credibility of the measures used. Inventories developed within the psychometric tradition are expected to provide theoretical and empirical evidence for the validity and reliability of the measures to support subsequent interpretations and decisions. These practices depend on a set of assumptions based on latent trait theory that are essential to understanding what psychometric measures can do. This tutorial outlines essential characteristics of design and reporting of psychometric self-report data.